Estimating Postural Control with the Balance Rehabilitation Unit: Measurement Consistency, Accuracy, Validity, and Comparison with Dynamic Posturography - Alahmari, Khalid A. (Arch Phys Med Rehabil, 2013)
OBJECTIVE: To examine the psychometric properties (test-retest reliability, concurrent validity, construct validity) of the Balance Rehabilitation Unit (BRU) during testing of sensory integration processes in healthy adults and individuals with vestibular disorders. DESIGN: Experimental cross-sectional design. SETTING: Vestibular disorders clinic. PARTICIPANTS: Participants (N= 90); 30 subjects with vestibular disorders (18 to 85 years); 30 young healthy adults (18 to 50 years); and 30 older healthy adults (60 to 85 years). INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: PARTICIPANTS WERE TESTED TWICE WITH THE BRU AND ONCE WITH THE SMART EQUITEST SENSORY ORGANIZATION TEST (SOT): The Center of Pressure (COP) was recorded in the anteroposterior (COP(ap)) and mediolateral (COP(ml)) directions. The COP(ap) and COP(ml) time series were used to estimate the COP area andvelocity. RESULTS: The intra-class correlation coefficient (ICC) of the BRU COP area and velocity measures for all subjects were at least 0.76 in all sensory organization conditions (p<.001). Significant correlations were found between the BRU and SOT, ranging from 0.64 to 0.81 for COP area and from 0.44 to 0.76 for COP velocity. The older control group had significantly greater COP area and velocity compared with the younger controls for BRU and SOT. COP (area, velocity) was significantly higher for the younger vestibular group compared with the younger controls. CONCLUSIONS: The reliability and validity of COP measurements obtained during testing of sensory integration processes were demonstrated using the BRU. Future work should examine the responsiveness of these measures when individuals with balance disorders participate in rehabilitation.